2011
DOI: 10.1016/j.tplants.2011.02.004
|View full text |Cite
|
Sign up to set email alerts
|

A framework integrating plant growth with hormones and nutrients

Abstract: It is well known that nutrient availability controls plant development. Moreover, plant development is finely tuned by a myriad of hormonal signals. Thus, it is not surprising to see increasing evidence of coordination between nutritional and hormonal signaling. In this opinion article, we discuss how nitrogen signals control the hormonal status of plants and how hormonal signals interplay with nitrogen nutrition. We further expand the discussion to include other nutrient-hormone pairs. We propose that nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
163
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(171 citation statements)
references
References 60 publications
6
163
1
1
Order By: Relevance
“…Nutrient sensing and hormonal signaling are interconnected in plants (Krouk et al, 2011), but little is known about whether or how the growth-promoting roles of photosynthesis and plant hormones are integrated. Exposure to elevated carbon dioxide (CO 2 ) enhances growth and results in a significant increase in sugar and starch content in Arabidopsis leaves (Teng et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient sensing and hormonal signaling are interconnected in plants (Krouk et al, 2011), but little is known about whether or how the growth-promoting roles of photosynthesis and plant hormones are integrated. Exposure to elevated carbon dioxide (CO 2 ) enhances growth and results in a significant increase in sugar and starch content in Arabidopsis leaves (Teng et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrate has profound effects on gene expression, hormone synthesis, and plant growth (Krapp et al, 2011;Krouk et al, 2011;Bouguyon et al, 2012) independent of its assimilation, demonstrating that it is sensed and signals cellular responses. Microarray analyses have shown that nitrate levels rapidly influence the expression of many classes of genes involved in their assimilation and metabolism (Wang et al, 2003;Scheible et al, 2004;Bi et al, 2007;Nero et al, 2009).…”
mentioning
confidence: 99%
“…In addition, the amount of N needed for plant growth is closely linked to the dry weight production (Krouk et al, 2011). Because of less favorable growth conditions, trees show lower growth in the colder site (BER) and it is possible that an addition of N has a greater effect.…”
Section: Nitrogen and Bud Burstmentioning
confidence: 99%